Evidence-based nursing practice readiness in tertiary hospitals in central China: a convergent parallel mixed methods study - Weihua Liu; Xiaohui Miao; Wenhui Bai; Yujie Wang; Yanwei Cheng; Hongmei Zhang (BMC Nursing)
Abstract Background Evidence-based nursing practice (EBNP) is essential for improving patient care and clinical outcomes. However, its successful implementation depends on both individual and organizational readiness. Comprehensive evaluations of EBNP readiness are limited in China, particularly studies using mixed methods to assess both personal and organizational preparedness. Methods A convergent parallel mixed methods design was used to evaluate EBNP readiness among 325 nurses in a tertiary hospital in central China. Quantitative data were collected using the Clinic Readiness to Evidence-Based Nursing Assessment (CREBNA) and Quick-Evidence-Based Practice-Value Implementation Knowledge (Quick-EBP-VIK) scales, while qualitative data were obtained from interviews with 7 nurses using the Community Readiness Model (CRM). The results of both methods were integrated to provide a comprehensive evaluation of readiness. Results Organizational readiness for EBNP, as measured by the CREBNA scale, was relatively strong, with a total score of 133.50 ± 16.45, accounting for 86.12% (133.5/155) of the full score. The highest score was in the organizational environment dimension (39.84 ± 5.31, 88.53%=39.84/45), followed by promoting factors (41.90 ± 6.18, 83.80%=41.9/50) and evidence (51.76 ± 6.67, 82.67%=51.76/60). In contrast, individual readiness, assessed through the Quick-EBP-VIK scale, was lower, with an overall mean score of 2.82 ± 0.67 out of 5. The value dimension had the highest score (4.08 ± 0.56, 81.6%=4.08/5), while knowledge (2.53 ± 0.99, 50.6%=2.53/5) and implementation (2.21 ± 0.90, 44.2%=2.21/5) were significantly lower. Qualitative findings from the CRM analysis indicated that overall readiness was at the preplanning stage, with leadership scoring 6.57 ± 1.62, while resources (3.79 ± 1.47) and community climate (3.71 ± 0.49) were at the vague awareness stage. Conclusions While organizational support for EBNP is well-established, individual readiness, especially in knowledge and implementation, remains low. Addressing this gap through targeted training and resource allocation is critical for advancing EBNP in China.